Ethnocultural basis of the formation process of the Crimean Tatar art culture and decorative and applied art (part two) - Ismet Zaatov (Крымское историческое обозрение)
In the articlean attempt is made to trace the course of the early medieval (Old Turkic) stage of Turkization process of the plain, foothill, mountainous, southern coast population of the Crimea. And also it follows the formation of artistic culture and decorative art of the Turkic ancestors of that period among the Crimean Tatars, preceding the appearance of the Kipchaks-Polovtsy-Kuman on the peninsula, as well as those occurring parallel to this process. Among the ethnic community of the descendants of the ancient autochthons of the peninsula, the Crimean mountainous people of the Tats, the common ancestors of the southern coast and mountain Crimean Tatars, as well as the ancestors of the Greco-Tatars – Urums of ethnocultural processes, who formed an ethnocultural whole with them.